The picture life of George Bush - Schneiderman, Ron frey50 (Franklin Watts New York, 1989)
Traces the life and accomplishments of the war hero, millionaire businessman, congressman, CIA director, and president of the United States.
Includes index
Keywords: Bush, George, -- 1924-; Pictorial works; Presidents -- United States -- Biography